2022
DOI: 10.1021/acsami.2c10947
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchal Porous Graphene-Structured Electrocatalysts with Fe–N5 Active Sites Modified with Fe Clusters for Enhanced Performance Toward Oxygen Reduction Reaction

Abstract: The local coordination environment around the active centers has a major impact on tuning the intrinsic activity of M–N–C catalysts. Herein, a porous graphene with Fe–N5 active sites modified with Fe clusters is successfully fabricated by using Fe3+-SCN– and NaHCO3 as the metal precursor and pore-forming agent, respectively. The unique Fe–N5 configuration accompanying Fe clusters and the improved ORR activity are confirmed by various characterization techniques and theoretical calculations. Benefiting from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Theoretical calculations and experimental studies have demonstrated that different coordination configurations of Fe-N x sites can influence the 3d electron distribution of iron centers, thus regulating the adsorption and desorption energy barriers of the ORR intermediate on Fe-N x sites to adjust the catalytic performance of Fe-N/C materials. , Different coordination configurations could be obtained by modulating the coordination numbers of Fe-N x sites (e.g., Fe-N 2 , Fe-N 3 , and Fe-N 5 , ), grafting axial ligands to Fe-N 4 sites (e.g., PFePc-I, Fe-N 4 -Cl, , and Fe-N 4 -OH), introducing dual-metal sites (e.g., Fe 2 -N 6 , Fe-Cu-N 6 , and Fe-N 4 -Bi-O), and coupling carbon defect to Fe-N x sites (e.g., edge Fe-N 4 and pentagon-bonded-Fe-N 4 ). Among them, edge Fe-N 4 sites have aroused wide concern among people for their structural stability as well as excellent catalytic activity. To form edge Fe-N 4 sites in Fe, N codoped carbon, the formation of edge carbon and construction of Fe-N 4 sites are essential steps.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical calculations and experimental studies have demonstrated that different coordination configurations of Fe-N x sites can influence the 3d electron distribution of iron centers, thus regulating the adsorption and desorption energy barriers of the ORR intermediate on Fe-N x sites to adjust the catalytic performance of Fe-N/C materials. , Different coordination configurations could be obtained by modulating the coordination numbers of Fe-N x sites (e.g., Fe-N 2 , Fe-N 3 , and Fe-N 5 , ), grafting axial ligands to Fe-N 4 sites (e.g., PFePc-I, Fe-N 4 -Cl, , and Fe-N 4 -OH), introducing dual-metal sites (e.g., Fe 2 -N 6 , Fe-Cu-N 6 , and Fe-N 4 -Bi-O), and coupling carbon defect to Fe-N x sites (e.g., edge Fe-N 4 and pentagon-bonded-Fe-N 4 ). Among them, edge Fe-N 4 sites have aroused wide concern among people for their structural stability as well as excellent catalytic activity. To form edge Fe-N 4 sites in Fe, N codoped carbon, the formation of edge carbon and construction of Fe-N 4 sites are essential steps.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36] Unfortunately, the electron penetration between SAs and NPs/ACs becomes really weak if the layer number of graphite carbon is greater than three, owing to the rapid decline in electron potential with thickness of graphite-carbon layer. 31,37 It suggests that the synergistic effects between metal SAs and metal NPs/ACs will also become more insignificant. 25,35,38 Furthermore, previous strategies for constructing these composite catalyst composed of metal SAs and NPs/ACs are typically to increase the metal content in the catalyst precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous investigations have demonstrated that the electronic interactions between SA sites and metal NPs/ACs can improve the intrinsic activity of SA sites, however, these synergies have only been proved in alkaline solution because these metal NPs/ACs are unstable in acidic media 25–30 . Currently, encapsulating these metal NPs and ACs into graphene layer is effective to enhance their ORR stability in an acidic medium 31–36 . Unfortunately, the electron penetration between SAs and NPs/ACs becomes really weak if the layer number of graphite carbon is greater than three, owing to the rapid decline in electron potential with thickness of graphite‐carbon layer 31,37 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rechargeable zinc-air batteries (ZABs) are highly preferred for their high specific energy density, security, and low contamination. However, their commercial application is constrained by the inefficiency of oxygen conversion processes at the air electrode. Currently, Pt-based catalysts are widely applied to oxygen reduction reaction (ORR). The atomic layer deposition (ALD) method was used to put the Pt nanoparticle load on CNTs by Gan et al, which obtained a Pt/CNT catalyst with excellent ORR catalytic activity. Meanwhile, Ru or Ir-based catalysts are applied to oxygen evolution reaction (OER). , A highly universal wet-chemical approach was used to prepare RuO 2 nanowires (NWs) by Yang et al, which showed a lower OER overpotential under acidic and alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%